PENGARUH LIVE STREAMING, FLASH SALE, DAN DOUBLE DAYS PROMOTION TERHADAP IMPULSIVE BUYING PADA PENGGUNA TIKTOK SHOP - Muslikha Irbah Zakiyah; M. Mustaqim; Achmad Zaki; Cynthia Eka Violita (JURNAL LENTERA BISNIS, 2025)
Digital technology advancements have significantly changed the e-commerce industry, particularly with the advent of interactive services like live streaming on TikTok. This studys aims to determine whether live streaming, flash sales, and double days promotions have a direct effect on consumer impulse purchases at TikTok Shop. This study employs a quantitative methodology. A total of 180 respondents who are active TikTok Shop users in Sidoarjo have filled out a questionnaire to provide data, which was then analyzed using SPSS. In this study, it was found that Live Streaming variable has no influence on Impulsive Buying. This is because live streaming is not strong enough to drive impulse purchases without attractive promotions. On the other hand, the Double Days Promotion and Flash Sale variables have a positive and significant effect on Impulsive Buying. This proves that flash sales and urgency-based promotional tactics can stimulate impulse purchases. These results provide insight for marketers to optimize promotional strategies on TikTok Shop to increase sales conversions.